2002
DOI: 10.1056/nejmoa020157
|View full text |Cite
|
Sign up to set email alerts
|

Mercury, Fish Oils, and the Risk of Myocardial Infarction

Abstract: The toenail mercury level was directly associated with the risk of myocardial infarction, and the adipose-tissue DHA level was inversely associated with the risk. High mercury content may diminish the cardioprotective effect of fish intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
376
3
7

Year Published

2003
2003
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 632 publications
(404 citation statements)
references
References 40 publications
10
376
3
7
Order By: Relevance
“…The levels of mercury found in our study were comparable to a similarly designed, recent study using ''control'' participants in eight European studies (Guallar et al, 2002) but lower than many early other studies (Suzuki et al, 1989;Garland et al, 1993;MacIntosh et al, 1997;Mortada et al, 2002;Yoshizawa, 2002;Joshi et al, 2003, p. 4). Temporal trends are one possible explanation; however, a larger study would be necessary to identify such trends in mercury levels.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The levels of mercury found in our study were comparable to a similarly designed, recent study using ''control'' participants in eight European studies (Guallar et al, 2002) but lower than many early other studies (Suzuki et al, 1989;Garland et al, 1993;MacIntosh et al, 1997;Mortada et al, 2002;Yoshizawa, 2002;Joshi et al, 2003, p. 4). Temporal trends are one possible explanation; however, a larger study would be necessary to identify such trends in mercury levels.…”
Section: Discussionsupporting
confidence: 76%
“…Numerous attempts have been made to identify and characterize useful biomarkers of exposure to mercury, including blood, urine, hair, fingernails and toenails, both as correlates of environmental exposures and also in relation to diseases such as coronary heart disease (e.g., Sinclair et al, 1980;MacIntosh et al, 1997;Guallar et al, 2002;Mortada et al, 2002;Yoshizawa et al, 2002). Toenail mercury concentrations are reasonably stable indicators of exposure over time (Garland et al, 1993) and toenails have the advantage over hair and fingernails of being less susceptible to external contamination.…”
Section: Introductionmentioning
confidence: 99%
“…35 Recent findings in adults suggest that MeHg exposure is associated with increased cardiovascular mortality. 46,47 Although several toxic mechanisms may be involved, these findings in conjunction with the present study suggest that the impact of neurotoxic MeHg effects on autonomic regulation of heart function deserves attention.…”
Section: Discussionsupporting
confidence: 73%
“…[9] Although inconclusive, recent studies have suggested that MeHg may promote or predispose to the development of heart disease. [10,11] Increased MeHg exposure was associated with adverse cardiovascular effects in adults [12][13][14] and children. [15] This paper reviews the human MeHg toxicology and the effects of MeHg exposure on neurobehavioural and cardiovascular outcomes, as based on human evidence from epidemiologic data.The paper also discusses issues in regard to exposure assessment and imprecision, and the relationship between the benefits from nutrients in fish and the risks associated with MeHg toxicity.…”
Section: Dr Grandjean Is Professor and Chair Of Environmental Medicinmentioning
confidence: 99%
“…Studies of the cardiovascular effect of Hg have used Hg levels in toenails and fingernails as biomarkers of Hg exposure, [11,55] although the extent that these reflect organic or inorganic Hg exposure is unclear. The fact that dentists have increased toenail Hg concentrations [11] would suggest that this biomarker reflects not only MeHg exposure.…”
Section: New Zealandmentioning
confidence: 99%